Trends in Suicide Mortality in Canada by Sex and Age Group, 1981 to 2017: A Population-Based Time Series Analysis: Tendances de la mortalité par suicide au Canada selon le sexe et le groupe d’âge, 1981 – 2017 : Une analyse de séries chronologiques dans la population - Varin, Mélanie (Can J Psychiatry, 2020)
OBJECTIVES: Suicide is a complex global public health issue. The objective of this study was to assess time trends in suicide mortality in Canada by sex and age group. METHODS: We extracted data from the Canadian Vital Statistics Death Database for all suicide deaths among individuals aged 10 years and older based on International Statistical Classification of Diseases and Related Health Problems, Ninth Revision (E950-959; 1981 to 1999) and International Statistical Classification of Diseases and Related Health Problems, 10th Revision (X60-X84, Y87·0; 2000 to 2017) for a 37-year period, from 1981 to 2017. We calculated annual age-standardized, sex-specific, and age group-specific suicide mortality rates, and used Joinpoint Regression for time trend analysis. RESULTS: The age-standardized suicide mortality rate in Canada decreased by 24.0% from 1981 to 2017. From 1981 to 2007, there was a significant annual average decrease in the suicide rate by 1.1% (95% confidence interval, −1.3 to −0.9), followed by no significant change between 2007 and 2017. From 1981 to 2017 and from 1990 to 2017, females aged 10 to 24 and 45 to 64 years old, respectively, had a significant increase in suicide mortality rates. However, males had the highest suicide mortality rates in all years in the study; the average male-to-female ratio was 3.4:1. CONCLUSION: The 3-decade decline in suicide mortality rates in Canada paralleled the global trend in rate reductions. However, since 2008, the suicide rate in Canada was relatively unchanged. Although rates were consistently higher among males, we found significant rate increases among females in specific age groups. Suicide prevention efforts tailored for adult males and young and middle-aged females could help reduce the suicide mortality rate in Canada.